Investigation of Buried HDPE Pipe Deflection Behavior - Kilic, Havvanur; Akinay, Emre (TURKISH CHAMBER CIVIL ENGINEERS, 2019)
In this study, the effects of pipe ring stiffness, vertical stress, fill placement relative compaction of fill placement and fill material type on deflection were investigated in buried high density polyethylene pipes (HDPE). In this content, field tests which are carried out to examine the behavior of flexible pipes placed under thick embankments for drainage purposes are used. Considering the pipe characteristics, fill placement, type of fill material, the results were examined by using Modified Iowa approaches and numerical analyses, and the obtained results were compared with the field measurements. As a result of comparisons, it is seen that the deflections computed from numerical analyses are in close agreement with the computed from the semi-emprical approaches that take in to deflections account the soil-pipe interaction. As a conclusion it is determines that the empirical approaches and two dimensional numerical analyses can be used in the design high density polyethylene pipes with low and high ring rigidity.
Keywords: HDPE pipe; deflections; Modified Iowa approachs; numerical analysis; Engineering